Phishing Attacks and Defenses - Chaudhry, Junaid Ahsenali; Chaudhry, Shafique Ahmad; Rittenhouse, Robert G. (International Journal of Security and Its Applications, 2016)
A phishing attack is a method of tricking users into unknowingly providing personal and financial information or sending funds to attackers. The most common phishing attacks use some form of electronic messaging such as email to provide a link to what appears to be a legitimate site but is actually a malicious site controlled by the attacker. Phishing is a hybrid attack combining both social engineering and technological aspects and combatting phishing attacks requires dealing with both aspects